An Experimental In Vivo Model to Characterize "Heavy Legs" Symptom in Topical Formulations - Pedro Contreiras Pinto; Luís Monteiro Rodrigues (Hindawi Limited, 2009)
The "Heavy legs" symptom is regarded as an early expression of chronic venous failure, estimated to affect 40% of the population in developing countries. A new methodology is proposed to approach the "tired or heavy legs" symptom. Seven females with this complaint applied a standard topical formulation during 28 days in one leg randomly chosen. Local blood flow records were obtained instantaneously and during postural change with a laser doppler flowmeter (LDF). High-frequency sonography and local morphometry were also obtained at Days 0, 14, and 28. When compared with D0, LDF values present a significant decrease of both basal and dynamical values after Day 14 and Day 28 suggesting that this effect may result from the formulation application, also involving the related massage. Centimetric measurements and sonographic analysis also supported those inferences. The proposed methodology can evaluate the dynamical changes of  "heavy legs" symptom and eventually be very useful to assess the related claim support.